Rapid Tests versus ELISA for Screening of HIV Infection: Our Experience from a Voluntary Counselling and Testing Facility of a Tertiary Care Centre in North India. (7th April 2014) - Mehra, Bhanu; Bhattar, Sonali; Bhalla, Preena; Rawat, Deepti
Abstract : Early and accurate diagnosis of human immunodeficiency virus (HIV) infection is essential for timely identification of patients needing antiretroviral therapy and for instituting HIV prevention strategies. The primary methodology for HIV testing has shifted from enzyme linked immunosorbent assay (ELISA) to rapid diagnostic tests (RDTs) in recent years, especially in resource limited settings. However, the diagnostic performance of RDTs is a matter of concern. In the present study the performance of an RDT being used as the initial test in serial testing based algorithm for HIV diagnosis was compared with ELISA. Seven hundred and eighty-seven sera, tested at the voluntary counselling and testing facility employing a serial testing algorithm (based on SD Bioline HIV-1/2 3.0 as the first test), were subsequently tested with Microlisa-HIV for anti-HIV antibodies. The first test missed 9 HIV reactive samples and also registered 5 false positives. The sensitivity, specificity, and negative and positive predictive values of the first test were 77.5%, 99.3%, and 98.8% and 86.1%, respectively, taking ELISA as the standard test. Our study highlights that RDTs fare poorly compared to ELISA as screening assays and that reactive results by RDTs need to be confirmed by western blot for a positive serodiagnosis of HIV infection.